PENDAMPINGAN PENGEMBANGAN WISATA DESA BUMDES DESA KAUMAN - Prasetyo, Deni Widyo (Transpublika Publisher, 2020)
The purpose of carrying out this community service activity is as an effort to find out how to improve the development of BUMDes Kauman village tourism. This research uses a qualitative descriptive research type. Data collection techniques are carried out by observation techniques, interviews, documentation. The technique of checking the validity of the data is through triangulation and continuous observation. Data analysis techniques using data reduction techniques, data presentation, drawing conclusions and verification. Livelihoods of local residents mostly work as entrepreneurs. Village tourism has benefits and benefits financially or it can be concluded that village tourism can help improve the economy of the people of Kauman Village. In other words, with village tourism, it can further improve the welfare of the community and the people of Kauman Village / participants in activities can understand the explanation of BUMDES Management material.